Vivienda rural bioclimatizada para mejorar el confort térmico en la zona altoandina - Vilca-Apaza, Henry-Mark (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
This book is an adaptation of a research presented at the National University of the Altiplano (Peru), it aimed to determine the efficiency of the design of the Bioclimatized Rural Housing Module to improve thermal comfort in the High Andean area of ​​Puno. The study was of an experimental type and quasi-experimental design with two groups, whose research techniques were observation and laboratory testing. The study population was made up of the set of bioclimatized rural housing modules that can be built in the Puno region; the sample, for a typical rural house of the district of Pichacani, province and department of Puno and a model of the bioclimatized rural house module elaborated at 1:10 scale. As a result, it was obtained that the Bioclimatized Rural Housing Module designed with adobe from the area and passive solar strategy (greenhouse) is effective in improving the thermal comfort of environments in the high Andean area, improving the internal temperature by 37% compared to the outside temperature and 27% compared to the typical adobe house in the area, reaching a comfort relative humidity of 56% in accordance with ASHRAE STANDARD 55. It is expected that the VRB Module can become a construction alternative in the areas Highlands of Peru.